Integrating Gender Issues in Disaster Risk Management Policy Development and in Projects - World Bank (World Bank, Washington, DC, 2017)
This note on integrating gender issues in disaster risk management (DRM) policy development and in projects is the second in a series of guidance notes on gender issues in DRM. The first part of this note looks at mainstreaming gender considerations into policy development. The second part focuses on the World Bank project cycle identifying entry points and providing practical advice and links to good practice examples. Grounded in extensive field work in Lao PDR and Vietnam, and drawing on the significant amount of material already available, these guidance notes are intended to be first stop, practical documents that can be used to design and implement gender dimensions into disaster risk management work across the EAP region. The target audience is World Bank staff, clients and development partners active in the fields of gender and DRM. DRM projects are informed and draw heavily on existing government policies and strategies to determine how best to meet the clients' development needs. Mainstreaming gender into the government's DRM policy and legal frameworks requires governments to create an effective enabling environment for gender equality and in cases where such environment already exists, identify and highlighting the policy entry points. Creating an enabling environment for gender equality often relies on a change in mindset and attitudes of many policy makers, which takes time. Improving information and awareness on gender and DRM, including existing policies, building the capacity of current and potential women policy makers, and providing more opportunities for women's participation in the DRM decision making process are some strategies that can be used to better address gender issues in Governments' DRM policies.